Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/ijgo.13330
|View full text |Cite
|
Sign up to set email alerts
|

Detection of types of HPV among HIV‐infected and HIV‐uninfected Kenyan women undergoing cryotherapy or loop electrosurgical excision procedure

Abstract: Objective: To assess the baseline types of HPV infection among HIV-positive and HIVnegative women in western Kenya undergoing cryotherapy or loop electrosurgical excision procedure (LEEP) for cervical intraepithelial neoplasia. Methods: A prospective observational study was conducted of baseline HPV characteristics of women undergoing visual inspection with acetic acid (VIA) and cryotherapy or LEEP. After a positive VIA in HIV-positive and HIV-negative women, data on demographics, CD4 count, and use of antiret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Though HPV is the main causative agent for cervical cancer, its prevalence and distribution vary in different geographical regions of the world. Several studies have shown HPV prevalence in Botswana and Kenya [2,16,25,[18][19][20][21][22][23][24][26][27][28]. However, the numbers of studies investigating the variants within HPV genotypes are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though HPV is the main causative agent for cervical cancer, its prevalence and distribution vary in different geographical regions of the world. Several studies have shown HPV prevalence in Botswana and Kenya [2,16,25,[18][19][20][21][22][23][24][26][27][28]. However, the numbers of studies investigating the variants within HPV genotypes are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in Africa have also explored the genomic diversity of HPV variants [12][13][14][15][16][17]. HPV genotypes − 16, -18, -45, and − 58 were observed among most cervical samples studied from Botswana and Kenya [2,16,25,[18][19][20][21][22][23][24][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Women between the ages of 18 and 45 years with an abnormal VIA examination were tested for HPV and treated with cryotherapy for lesions not suspicious of cancer [ 38 ]. Colposcopy and biopsy were performed in women with suspicious lesions, and LEEP was performed if biopsy showed CIN2/3.…”
Section: The Consortium Version 1: “Hpv and Cervical Cancer In Kenyan...mentioning
confidence: 99%
“…Cervical cancer has the highest mortality of gynecologic cancers in Kenya [ 1 ]. The estimated prevalence of human immunodeficiency virus (HIV) in Kenya is 4.0% and majority of adult PWH in Kenya are women (63.5%) [ 2 ]. The high incidence of HIV and human papillomavirus (HPV) coinfection that could progress to cervical cancer raises the priority of this disease burden.…”
mentioning
confidence: 99%